Intestinal Immune Deficiency and Juvenile Hormone Signaling Mediate a Metabolic Trade-off in Adult Drosophila Females. - Shianiou, G.; Teloni, S.; Apidianakis, Y. (Metabolites, 2023)
A trade-off hypothesis pertains to the biased allocation of limited resources between two of the most important fitness traits, reproduction and survival to infection. This quid pro quo manifests itself within animals prioritizing their energetic needs according to genetic circuits balancing metabolism, germline activity and immune response. Key evidence supporting this hypothesis includes dipteran fecundity being compromised by systemic immunity, and female systemic immunity being compromised by mating. Here, we reveal a local trade-off taking place in the female Drosophila midgut upon immune challenge. Genetic manipulation of intestinal motility, permeability, regeneration and three key midgut immune pathways provides evidence of an antagonism between specific aspects of intestinal defense and fecundity. That is, juvenile hormone (JH)-controlled egg laying, lipid droplet utilization and insulin receptor expression are specifically compromised by the immune deficiency (Imd) and the dual oxidase (Duox) signaling in the midgut epithelium. Moreover, antimicrobial peptide (AMP) expression under the control of the Imd pathway is inhibited upon mating and JH signaling in the midgut. Local JH signaling is further implicated in midgut dysplasia, inducing stem cell-like clusters and gut permeability. Thus, midgut JH signaling compromises host defense to infection by reducing Imd-controlled AMP expression and by inducing dysplasia, while midgut signaling through the Imd and Duox pathways compromises JH-guided metabolism and fecundity.